Internal and External Factors on the Performance of Halal Food MSMEs in Bekasi Regency - Widyastuti, Tri; Rianto, Muhammad Richo; Pitoyo, Bayu Seno (Jurnal Manajemen Bisnis, 2024)
This study analyzes the performance of halal food MSMEs in Bekasi Regency. Internal factors of information technology and external factors of cooperation influence the performance of MSMEs. The unit of analysis in this study amounted to 100 halal food MSME players in Bekasi Regency. The findings in this study further strengthen the findings of previous studies where internal factors of information technology affect the performance of MSMEs with a p-value of 0.009 and external factors of cooperation affect the performance of MSMEs with a p-value of 0.000. This study further strengthens previous findings regarding information technology and cooperation. This research is new to previous research conducted on the halal food industry in the Bekasi district. The selection of internal variables with the Resource Base View (RBV) and Market Base View (MBV) theories is a novelty in this study.